2008
DOI: 10.1053/j.ajkd.2008.02.306
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Podocin R229Q Polymorphism With Increased Albuminuria or Reduced Estimated GFR in a Large Population-Based Sample of US Adults

Abstract: Background-Rare mutations in nephrosis 2 (NPHS2), encoding podocin, are found in patients with familial and sporadic steroid resistant nephrotic syndrome and focal segmental glomerular sclerosis. The objective of this study was to assess the contribution of the commonly reported functional podocin polymorphism R229Q to kidney disease in the population-at-large and to replicate a prior study of an association of R229Q and albuminuria in the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 26 publications
(5 reference statements)
0
22
0
Order By: Relevance
“…Additionally, Pereira et al [8] reported that R229Q is responsible for microalbuminuria in the general population. On the other hand, Kottgen et al [14] did not corroborate any significant association between R229Q and GFR in either white or black individuals. Based on a very detailed review and meta-analysis by Franceschini et al [15], the R229Q variant gives a nonsignificant increased risk for FSGS by 20-70% in European descent populations.…”
Section: Resultsmentioning
confidence: 88%
“…Additionally, Pereira et al [8] reported that R229Q is responsible for microalbuminuria in the general population. On the other hand, Kottgen et al [14] did not corroborate any significant association between R229Q and GFR in either white or black individuals. Based on a very detailed review and meta-analysis by Franceschini et al [15], the R229Q variant gives a nonsignificant increased risk for FSGS by 20-70% in European descent populations.…”
Section: Resultsmentioning
confidence: 88%
“…In contrary, Tonna et al [33] found that p.Arg229Gln does not alter the risk of proteinuria in the general population. Köttgen et al [34] did not corroborate any significant association between p.Arg229Gln and GFR in either white or black individuals. Based on a very detailed review and meta-analysis article by Franceschini et al [35], the p.Arg229Gln variant gives a non-significant increased risk for FSGS by 20 to 70% in populations of European descent.…”
Section: Discussionmentioning
confidence: 94%
“…Kottgen et al [16] did not find a significant association of this sequence variant and albumin-creatinine ratio or estimated glomerular filtration rate in either white or black individuals. However, a recent study suggests that patients carrying this sequence variant, in combination with a pathogenic NPHS2 mutation develop FSGS [17,18].…”
Section: Discussionmentioning
confidence: 98%